EVALUASI BATUAN INDUK FORMASI TALANG AKAR ATAS BERDASARKAN DATA GEOKIMIA DI DESA BUKIT SUBAN, KABUPATEN SAROLANGUN, SUB-CEKUNGAN JAMBI - Alfayed, Muhammad Rus Dody; Riyadi, Hasan; Zelandi, Muhammad; Siregar, Yusmansyah; Syaifudin, M. (Petro : Jurnal Ilmiah Teknik Perminyakan, 2025)
Our oil and gas exploration must be able to understand the concept of the petroleum system. Source rock is one of the most important parameters in the petroleum system that functions as a hydrocarbon producer or source rock, even placing the bedrock as the number one priority that must be present in the petroleum system (Magoon and Dow, 1994). This study aims to determine the potential of parent rocks in the Upper Talang Akar Formation in the research area to produce hydrocarbons. The research method was carried out using surface samples, geochemical analysis of Total Organic Carbon, Rock-Eval Pyrolysis and Vitrinite Reflektance. Based on the results of geochemical analysis research that has been carried out on the source rock of the Upper Talang Akar Formation, the characteristics of the potential of the source rock in producing hydrocarbons have a rich organic material range (1.38 – 4.06), based on TOC data, the sample of the source rock of the Upper Talang Akar Formation has quite good potential. Analysis of organic material types in the study area's source rock samples yielded kerogen types II and III that have the potential to produce oil and gas hydrocarbons. The maturity level analysis is based on Tmax data of the Upper Talang Akar Formation source rock has an immature maturity level and based on Ro data, the upper Talang Akar of the source rock has an immature maturity level. Therefore, it can be concluded that the shale source rock of the Upper Talang Akar Formation in the research area has the potential to produce good to very good hydrocarbons and produce oil and natural gas in the immature phase.